Golanudiplosis japonicus - a new midge attacking comstock mealybug in Japan (Diptera: Itonididae). - Grover, P.; Prasad, S. N. (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The midge found attacking eggs of the comstocki mealybug, Pseudococcus comstocki, in Japan is described as a new genus Golanudiplosis with japonicus as its type species. Both male and female are described in detail and their systematic position is discussed. Nomenclatural Actsjaponicus Grover & Prasad, 1968 (Golanudiplosis), spec. n.Golanudiplosis Grover & Prasad, 1968 (Itonididae), gen. n.